(3eSfO GdEeGe CMeO Hf MfHds - (3GdTjHGfj, GdeQhRj, GdHZOGOj, CHh YHO Gddg, CMeO Hf eMeO Hf MfHd, J (B241(3g`s
(3ChdgG (B:s
(3bGd (B: (3eG ef eSde jehJ jhe GdLeYI Ch djdI GdLeYI EdG hbGg Gddg aJfI GdbHQ MOKfG YHO Gddg MOKfj CHj KfG SdjeGf Hf MQH , KfG MeGO Hf RjO , Yf GdUbYH Hf RgjQ , Yf RjO Hf CSde , bGd MeGO , CXfg Yf YWGA Hf SjGQ (B( (3cPG (B)s
(3BNQgG (B:s
(3MOKfG YHO Gddg MOKfj CHj KfG jMji Yf SajGf bGd MOKfj SYO Hf EHQGgje Yf GdCYQL Yf CHj gQjQI hGHfYaQ bGd (B: (3KfG TYHI Yf eMeO Hf RjGO bGd SeYJ CHG gQjQIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B1 / 203s
(3eYLe GdeDdajf (B1 / 261s
(3cTa GdXfhf (B2 / 1680s
(3JGQjN GdESdGe (B/ (3hajGJ (B241s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdMOjK hGdeUWdMs